Zahlung der Jüdenvermögensabgabe aus Sperrguthaben (1938)
An article clipping from the Frankfurter Zeitung, a German-language newspaper published from 1856 to 1943. In Nazi Germany, it was considered the only mass publication not completely controlled by the Propagandaministerium under Joseph Goebbels.
Keywords: Antisemitism; Newspapers; Clippings (Books, newspapers, etc.); German newspapers; Third Reich; Frankfurter Zeitung und Handelsblatt (Frankfurt am Main, Germany : Daily)